An unusual first presentation of hypopharyngeal carcinoma as thyroid abscess: Case report of a diagnostic challenge - Heng Yao Tan; Siti Hajar Sanudin; Sai Guan Lum; Eugene Hung Chih Wong (Elsevier Ltd, 2021)
Hypopharyngeal carcinoma can involve thyroid gland due to their close proximity. However, an initial presentation as a thyroid abscess is rare in this malignancy. To our knowledge, this is the second reported case in the English literature. CASE We described a 45-year-old female who presented with dysphagia, hoarseness and anterior neck swelling. The initial CT scan revealed a right thyroid abscess which was incised and drained with no malignancy found in the biopsy of the thyroid tissue. Patient presented one month later with worsening dysphagia, weight loss and a fungating anterior neck mass. Further investigation revealed a locally advanced hypopharyngeal squamous cell carcinoma extending to the right thyroid, upper oesophagus, prevertebral muscles and bilateral cervical lymph nodes (T4bN2cM0). Unfortunately, the patient passed away prior to initiation of treatment. linicians should have raised index of suspicion of a possible underlying hypopharyngeal carcinoma in patients presenting with thyroid abscess and proceed to further investigations in order to ensure early diagnosis and treatment of the malignancy.